Inventaire des especes de mouches des fruits (Diptera Tephritidae) sur goyave dans la religion de yaounde au Cameroun - Ndzana Abanda, F.X.; Quilici, S.; Vayssières, Jean-François; Kouodiekong, L.; Woin, N. (EDP Sciences, 2008)
The aim of this study was to identify the main species of fruit flies (Diptera, Tephritidae) of economic importance in guava orchards in the central province of Cameroon. Materials and method. This work was completed in three localities (Yaounde, Bikok and Essé) of the wetland area of Cameroun. A total of 270 infested guava fruits was collected and monitored for emergence of fruit flies. Results. The collected fruits made it possible to collect 1260 puparia, from which three species of fruit flies were identified: Ceratitis anonae, which accounted for 64% of the adults obtained, Bactrocera invadens (35%) and B. mesomelas (1%). The first two species, present in the three localities investigated, are of economic importance. B. invadens is a new invasive species for Cameroon, while B. mesomelas, not observed around Yaounde, has lately been reported in this country. Conclusion. This first inventory will have to be followed by a study on the distribution of these species, their host-plant range, the evolution of their populations and their natural enemies. More specific complementary studies should make it possible to improve knowledge on the species of the fruit flies in Cameroon in order to develop an integrated management of these important pests.